2019
DOI: 10.28991/cej-2019-03091416
|View full text |Cite
|
Sign up to set email alerts
|

Study Numerical Simulation of Stress-Strain Behavior of Reinforced Concrete Bar in Soil using Theoretical Models

Abstract: Nonlinear analysis for reinforced concrete members (R.C.) with two types of bars also with unsaturated and saturated soils was used to represent the models. To control the corrosion in the steel bar that used in R.C. member and decrease the cost, the geogrid with steel bar reinforcement are taken in this study to determine the effect of load-deflection and stress-strain relationships. The finite element method is used to model the R.C. member, bars and soil. A three-dimensional finite element model by ABAQUS v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The finite element model is used to represent the reinforcement in the foundation with two types of soil [1].…”
Section: Generalmentioning
confidence: 99%
See 2 more Smart Citations
“…The finite element model is used to represent the reinforcement in the foundation with two types of soil [1].…”
Section: Generalmentioning
confidence: 99%
“…Geogrid can be used as a reinforcement in foundation with or without steel bar reinforcement, and that has an advantage by used with saturated and unsaturated soil. That means the geogrid reinforcement with a foundation in soil with liquid can satisfy the sustainability [1]. Widely used geosynthetics for sealing, separation, and protection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is high spiking at the startup of transient response in the case of FESO-based ADRC, while this chartering disappears in the profile of RESObased ADRC. This study can be extended for future work either by including recent observation techniques or to design other control schemes either for enhancing the ADRC or for comparison in performance (Hameed, 2017;Humaidi et al, 2018b;Sánchez et al, 2021;Humaidi & Hameed, 2019a;Laaraba & Khechekhouche, 2018;Humaidi & Abdulkareem 2019b;Pourmahmoud et al, 2014;Humaidi et al, 2018c;Amli et al, 2020;Humaidi etal., 2021;Naima et al, 2018;Ajel et al, 2021;Mahmoud, 2021;abed et al, 2021;Bahatmaka & Kim, 2019;Al-Qadami et al, 2020).…”
Section: Case Ii: Clinical Reference Inputmentioning
confidence: 99%
“…Considering several studies reported in the literature [12,[22][23][24][25][26][27][28][29], it was decided to choose the used finite element model Solid65, Solid185 and Link8 finite elements of the Ansys code [16]. The ANSYS code defined Solid65 as concrete in 3-D solid modelling with reinforcing bars for its ability to crack in tension and crush in compression.…”
Section: General Configuration Of the Composite Columns And Boundary Conditionsmentioning
confidence: 99%